STUDY OF GENUS CHEIROCHELA (NAUCORIDAE) FROM DIFFERENT PART OF INDIA - SHOEB, MOHAMMAD (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Naucoridae is a small family of aquatic insect of sub order Heteroptera. The member of family Naucoridae are easily distiguished due to broad, oval and flattned body. The study of Indian naucoridae is of a great importance. The genus cheirochela is previously record by two species cheirochela assamensis hope, 1841 and Cheirochela Feena, Montand 1897. A new species of the genus is being discovered for the first time in its current state. The current study is the result of a three-and-a-half-year continuous survey of these bugs in various locations of India. Several field surveys were conducted in Uttar Pradesh, Punjab, Haryana, Delhi, Assam, and Rajasthan to gather a significant number of bugs from ponds, lakes, rivers, streams, and water reservoirs in various parts of India. The genital propagation of the new species was made and examined. The insect of this study were preserved in 90% Alcohal. The study was made under binoculars, stereoscope and compound microscope, camera lucida were used for making the sketches and measurements were taken with the halp of micrometer.